VD_FINDINFO Décision / 2012 / 31 vom 4. November 2011 - VD Tribunal cantonal (2011)
CLASSEMENT DE LA PROCÉDURE, FRAIS DE LA PROCÉDURE, PRÉSOMPTION D'INNOCENCE | 319 CPP (CH), 393 al. 1 let. a CPP (CH), 426 al. 2 CPP (CH)